Practices for supporting relatives of patients in the agonal phase by an interdisciplinary team in palliative care units. consensus research (PROPAGE 2) - M. Mélin; C. Roumiguière; M. Frasca; V. Berger; H. Hoarau; B. Paternostre; N. Stadelmaier; O. Pic; V. Bergua; PROPAGE 2 Group; H. Amieva; B. Burucoa (BMC Palliative Care)
Summary Context In the absence of existing recommendations, the objective of this study was to establish a consensus of the support practices used in an interdisciplinary team in a palliative care unit (PCU) for the relatives of patients in the agonal phase. Method This is a consensus study using the Delphi technique. 40 French PCUs participated in this study, including 204 professionals (nurses, nursing assistants, doctors, psychologists, social workers), 42 support volunteers and 32 relatives. These experts responded to a questionnaire comprised of a list drawn up from the results of a preliminary study conducted at Bordeaux University Hospital of 55 practices organised around four topics: providing care and ensuring comfort; communicating, informing and explaining; interacting; and mobilising interdisciplinarity skills. Results Thirty-five practices were approved by the agreement of professionals, volunteers and relatives. 11 were approved only by professionals/volunteers and 6 only by relatives. Three practices were deemed inappropriate by participants. Conclusions These results highlight consensual practices of care during agonal phase in specialized palliative care services and the importance of the quality of care given to patients, of counselling, and the attention paid to the relatives themselves. They will guide and enrich training modules for teams working with relatives.